Sistem Perkawinan dan Pewarisan pada Masyarakat Hukum Adat Rejang Provinsi Bengkulu - Arso, Dimas Dwi; APHA, Journal Manager (Jurnal Hukum Adat Indonesia, 2018)
This study aims to find out the marriage and inheritance system in the Rejang Customary Law community of Bengkulu Province. This research is descriptive analysis. In this study will describe and analyze the marriage and inheritance system of the Rejang Customary law community in Bengkulu Province. This study uses a normative approach, which is done by conducting a study of library materials both primary, secondary and tertiary legal materials in order to obtain answers about marriage and inheritance to the Rejang Customary law community. The data obtained in this study analyzed by using qualitative analysis and the output is descriptive analysis data, in this study qualitative analysis was carried out with inductive deductive thinking methods and vice versa to describe the marriage and inheritance system of the Rejang Customary law community in Bengkulu Province. Research results show that for the rejang tribe, the marriage ceremony is a place to show strength (both wealth and the large number of families) as well as a sign of sanctity. The marriage ceremony is the last ceremony held by parents towards each of their children. It could also be said to be a ceremony of "releasing debt" the obligation of parents to children. In the Adjang Indigenous marriage system, the Rejang tribe adheres to the eleutherogami marriage system. This can be seen from the absence of necessities or prohibitions such as the endogamous marriage system and the exogamous marriage system. The Rejang Indigenous Community has a major inheritance system in which sole control over inheritance in the hands of the oldest male child. If the child sells or pawns inheritance that has not been divided, not the arena of a legitimate authority, then the action can be prosecuted by his other brothers because in principle each individual has the right to inherit from the assets of his parents. But in the current changes, there is also a division of inheritance in the Rejang Indigenous people carried out by an individual distribution system, namely inheritance is divided into each individual as heirs and for the future will be in the mastery and management of each individual heir.